The Modality Systems in Lawyer and Witness’s Utterances on Courtroom Questioning of Legal Discourse - Ramadhani, Reski; Amalia, Rosaria Mita; Indrayani, Lia Maulia; Mahdi, Sutiono (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The use of Systemic Functional Linguistics proposed by Halliday and Matthiessen (2004) is rarely applied mostly in courtroom discourse analysis. This article presents the analysis of modality system used in the lawyer and witness’s utterances on courtroom questioning in cross-examination. The main focus is to explore the lawyer’s linguistic power to examine the facts given by the witness. Applying the interpersonal grammatical metaphor, the utterances are evaluated based on the different types, orientations, and values of modality in order to show a powerful position and to convince the jury toward the facts. This is a case study employed a qualitative method with a descriptive approach. The data are taken from the transcriptions of the courtroom questioning between the lawyer and the witness of Michigan V Charles Warren’s case from YouTube (2015). This case study revealed that most of the utterances produced by the lawyer contain a higher and more medium value of modality system. Then, the way he states the argument tends to be more objective. On the other hand, the witness tends to use medium and low modality system. In answering the questions, subjectivity is employed more by the witness which indicates that he has a personal attitude toward the state of affairs. It can be indicated that the lawyer has more linguistic power by applying more high value of modality system which means that he makes the facts strongly clearer toward the state of affairs at the time. The implication of this research is expected to give the information to the reader on how language can provide power to the user especially for the lawyer in order to examine the facts given by the witness